2012
DOI: 10.1002/brb3.87
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of synergistic muscle activity following neuromuscular electrical stimulation of one muscle

Abstract: The aim of the study was to determine muscle activation of the m. triceps surae during maximal voluntary contractions (MVCs) following neuromuscular electrical stimulation (NMES) of the m. gastrocnemius lateralis (GL). The participants (n = 10) performed three MVC during pretest, posttest, and recovery, respectively. Subsequent to the pretest, the GL was stimulated by NMES. During MVC, force and surface electromyography (EMG) of the GL, m. gastrocnemius medialis (GM), and m. soleus (SOL) were measured. NMES of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Thus, we conclude that force compensating mechanisms occurred. Force compensation during voluntary contraction after fatigue of a single muscle has also been reported in the literature (Akima et al, 2002;de Ruiter, Hoddenbach, Huurnink, & de Haan, 2008;Stutzig et al, 2012). For the triceps surae it was reported that the bi-articular GL can be compensated for by its synergistic muscles (Stutzig & Siebert, 2015), which is in agreement with the results of the present study (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, we conclude that force compensating mechanisms occurred. Force compensation during voluntary contraction after fatigue of a single muscle has also been reported in the literature (Akima et al, 2002;de Ruiter, Hoddenbach, Huurnink, & de Haan, 2008;Stutzig et al, 2012). For the triceps surae it was reported that the bi-articular GL can be compensated for by its synergistic muscles (Stutzig & Siebert, 2015), which is in agreement with the results of the present study (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…For example, it was observed that fatigue of a single muscle can be compensated for by synergistic muscles resulting in unchanged synergistic muscle forces (Akima, Foley, Prior, Dudley, & Meyer, 2002;Stutzig & Siebert, 2015;Stutzig, Siebert, Granacher, & Blickhan, 2012). Stutzig et al (2012) and Stutzig and Siebert (2015) fatigued the gastrocnemius lateralis (GL) solely and observed increased synergistic (soleus, gastrocnemius medialis) muscle activities (about 10%) during isometric maximum voluntary contractions (MVC: maximal contraction that a subject accepts as maximal and that is produced with appropriate continuous feedback of achievement (Gandevia, 2001)). Similar results have been reported by Akima et al (2002) who fatigued the vastus lateralis.…”
Section: Introductionmentioning
confidence: 96%
“…This increase was in response to NMES of the GL. Increased muscle activity of synergistic muscles after NMES of 1 muscle has also been reported . Akima et al .…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that fatigue of a single muscle leads to increased muscle activity in synergistic muscles during voluntary contractions . This observation was identified for different muscle groups and is interpreted to be a compensating effect . It is assumed that the force‐compensating effects of synergistic muscles depend on muscle length …”
mentioning
confidence: 99%
“…The triceps surae is a muscle that is frequently examined in neuromuscular research . This muscle consists of the soleus (SOL), lateral gastrocnemius (LG), and medial gastrocnemius (MG) muscles.…”
mentioning
confidence: 99%